The effect of delivery mode on maternal and newborn comfort: An analytical study (Annals of Medical Research, 2021)
Aim: This study was conducted to evaluate the effect of delivery mode on maternal and newborn comfort. Material and Methods: It is an analytical study. 60 mothers who had vaginal delivery and 60 mothers who had caesarean section and their newborn infants.It was conducted in a State Hospital located in a province in the southern Turkey. The data of the study were collected with Mother and Newborn Information Form, the Postpartum Comfort Questionnaire, the Newborn Comfort Behavior Scale, and the Breastfeeding Self-Efficacy Scale. Before starting the study, written and verbal permissions were obtained from the institution, the ethics committee and the mothers.Results: In this study, it was determined that those who had a caesarean delivery experienced more problems related to sitting on the bed, standing up, personal hygiene, perineal hygiene, urinary incontinence, flatus, and pain at the operation site compared to those who had a vaginal delivery (p0.05). The breastfeeding self-efficacy scores did not differ between the two groups (p>0.05). Conclusions: Future studies should evaluate the effect of the method of delivery on maternal and newborn comfort.According to the literature, women who had vaginal delivery according to cesarean section; postpartum comfort, breastfeeding success and self-efficacy of breastfeeding were reported to be higher. In this study, it was determined that the delivery mode did not affect the maternal and newborn comfort and mother’s breastfeeding self-efficacy.
Keywords: Delivery mode; maternal comfort; newborn comfort